2020
DOI: 10.1136/bmjopen-2020-038649
|View full text |Cite
|
Sign up to set email alerts
|

Treatment success of internet-based vestibular rehabilitation in general practice: development and internal validation of a prediction model

Abstract: ObjectivesTo develop and internally validate prediction models to assess treatment success of both stand-alone and blended online vestibular rehabilitation (VR) in patients with chronic vestibular syndrome.DesignSecondary analysis of a randomised controlled trial.Setting59 general practices in The Netherlands.Participants202 adults, aged 50 years and older with a chronic vestibular syndrome who received either stand-alone VR (98) or blended VR (104). Stand-alone VR consisted of a 6-week, internet-based interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Technological advances, such as wearable technologies linked to electronic records present opportunities for addressing the problems of symptom control and improved adherence to prescribed exercise programs. Web based VPT has been shown to be effective in chronic dizziness ( 20 , 21 ) but does not address the problem of accurately measuring adherence or providing biofeedback during exercise. Sensors such as accelerometers, and gyroscopes allow human physiological signals to be encoded and recorded, allowing health professionals to measure patient exercise performance and adherence in ways that were not possible previously.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances, such as wearable technologies linked to electronic records present opportunities for addressing the problems of symptom control and improved adherence to prescribed exercise programs. Web based VPT has been shown to be effective in chronic dizziness ( 20 , 21 ) but does not address the problem of accurately measuring adherence or providing biofeedback during exercise. Sensors such as accelerometers, and gyroscopes allow human physiological signals to be encoded and recorded, allowing health professionals to measure patient exercise performance and adherence in ways that were not possible previously.…”
Section: Introductionmentioning
confidence: 99%
“…Web‐based VR is an approach available in English and Dutch versions. Randomized trials have shown that web‐based VR, standing alone or combined with face‐to‐face physiotherapy support, is safe and clinically effective (Geraghty et al., 2017 , 2014 ; van Vugt et al., 2017 , 2019 , 2020 ). These RCTs have recruited primary care participants with a relatively low symptom burden (van Vugt et al., 2017 ; Yardley et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Es difícil predecir, si el modelo de rehabilitación vestibular que incluye ejercicios terapéuticos más intervención basada en internet o el modelo que incluye además al fisioterapeuta, es el que tiene más éxito para la rehabilitación del síndrome vestibular crónico por hipofunción vestibular (89), está demostrado que ambos modelos son clínicamente efectivos y seguros (90).…”
Section: Aspectos éTicosunclassified